Preventive effects of ketone ester BD-AcAc(2) on central nervous system oxygen toxicity and concomitant acute lung injury - Yi, Hongjie (The Journal of the South Pacific Underwater Medicine Society and the European Underwater and Baromedical Society, 2018)

(untitled) (Diving Hyperb Med)
BACKGROUND: Recent studies indicated that ketone ester R,S-1,3-butanediol acetoacetate diester (BD-AcAc(2)) may be effective in preventing central nervous system oxygen toxicity (CNS-OT) and concomitant acute lung injury, a serious medical problem to be faced when breathing hyperbaric oxygen (HBO). This study aimed to further investigate the protective effects of BD-AcAc(2) against CNS-OT and concomitant acute lung injury (ALI) in mice. METHODS: Mice were treated with BD-AcAc(2) in peanut oil vehicle (2.5, 5.0 or 10.0 g·kg(-1) body weight) by gavage 20 minutes before 600 kPa HBO exposure. Control mice received the vehicle only. Seizure latency was recorded. Malondialdehyde content in brain and lung tissues, total protein level in bronchoalveolar lavage fluid (BLF) and lung water content were measured 60 minutes after the hyperbaric exposure. Histopathology of lung tissue was undertaken. RESULTS: Compared with the vehicle alone, BD-AcAc(2) prolonged seizure latency in a dose-dependent manner (P < 0.01). The HBO-induced increase in brain malondialdehyde, BLF protein and lung water were significantly reduced by BD-AcAc(2) (P < 0.01). CONCLUSION: Oral administration of the ketone ester BD-AcAc(2) significantly protected against CNS-OT and concomitant ALI. Alleviation of oxidative stress may be one underlying mechanism providing this effect.